Short-term outcome of levamisole in frequently relapsing nephrotic syndrome: a single-center prospective cohort study - Khatri, Sabeeta; Bajeer, Irshad Ali; Zubair, Aasia; Lanewala, Ali Asghar Anwar; Hashmi, Seema (Frontiers in Nephrology, 2025)
IntroductionThis study aims to describe the outcome of levamisole (LEVA) treatment in children with frequently relapsing nephrotic syndrome (FRNS).MethodsThis prospective cohort study was conducted at the Department of Pediatric Nephrology, Sindh Institute of Urology and Transplantation from 1 January 2019 to 31 December 2020. Children aged 1–18 years diagnosed with FRNS were included. LEVA was started with a dose of 2–2.5 mg/kg every other day for 2 years along with low-dose prednisolone in the first year.ResultsA total of 70 children with FRNS were enrolled in the study. The median age was 7.5 [interquartile range (IQR) 5.0–9.6 years] with a slight predominance of boys (42, 60%). The mean number of relapses and cumulative dose of steroids significantly decreased after 2 years of LEVA therapy and during the 1-year follow-up. LEVA non-response was observed in half of the studied participants (28, 46%). The responders and non-responders were comparable in terms of cumulative dose of steroids and number of relapses in the year prior to starting LEVA [5,242 ± 1,738 versus 4,910 ± 1,469 (p-value = 0.52) and 5.4 ± 2.4 versus 5.2 ± 2.1 (p-value = 0.85)].ConclusionLEVA therapy resulted in a substantial reduction in the frequency of relapses and cumulative dosage, indicating its potential as an alternative option for children with relapsing disease.